Inovasi Pembelajaran di Sekolah Dasar: Tinjauan Observasional Terhadap Kreativitas dan Implementasi Kurikulum Merdeka Di SD Pupuk Kujang - Afridha Laily Alindra; Ica Nurlaela; Kania Pratiwi; Khaerani Nurfaoziah; Khalishah Nurul Salamah; Mayang Gita Fitriani; Paola Pebriyanti (Departement of Mathematics Education, 2023)
This journal reviews Learning Innovations on Creativity and Implementation of the Independent Curriculum at Pupuk Kujang Elementary School. This research aims to describe learning innovation, learning creativity, and the impact of this innovation on the character of students at Pupuk Kujang Elementary School. This type of research is qualitative research with observation instruments, interview guides, and questionnaires filled out by grade 5 students. The data sources for this research are the results of interviews with grade 5 guardians, interviews with grade 5 students, and questionnaires. As a result of these interviews, researchers found that there were many innovations implemented at Pupuk Kujang Elementary School, such as planting activities, technological engineering, and literacy weeks. There are extracurriculars such as coding, robotics, sports, arts, and tahfidz. The impact of these activities allows students to develop many abilities and increase productivity at school. Students are also motivated to apply their abilities in everyday life.